2009
DOI: 10.1080/02699050902926325
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between the WNSSP and therapeutic participation in adolescents in low response states following severe traumatic brain injury

Abstract: These results suggest that scores on the WNSSP may be related to the return of communication skills in adolescents in low response states as one part of assessing their therapeutic participation and ultimate rehabilitation readiness. This ability may assist in making decisions regarding care planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…This sample size was ‘middle of the range’ when compared with other WNSSP studies specifically focussed on severe TBI (e.g. Ansell & Keenan, ; n = 57; Gill‐Thwaites & Munday, ; n = 60; Lammi et al ., ; n = 18; Patrick et al ., ; n = 10; Smith et al ., , n = 25). Data were extracted from medical records that were prepared for clinical, not research purposes consequently missing data was a problem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sample size was ‘middle of the range’ when compared with other WNSSP studies specifically focussed on severe TBI (e.g. Ansell & Keenan, ; n = 57; Gill‐Thwaites & Munday, ; n = 60; Lammi et al ., ; n = 18; Patrick et al ., ; n = 10; Smith et al ., , n = 25). Data were extracted from medical records that were prepared for clinical, not research purposes consequently missing data was a problem.…”
Section: Resultsmentioning
confidence: 99%
“…Validity studies by test developers found the WNSSP and RLAS correlation was strong ( r = 0.73, P < 0.001, 95% CI, P = 0.001) as was the correlation with Sensory Modality Assessment and Rehabilitation Technique (SMART) (Gill‐Thwaites, ) total scores ( r = 0.7). More recently, the WNSSP was correlated with expert judgement regarding participation of subjects in video‐taped communication, arousal and awareness behaviour (Patrick et al ., ). Here, the WNSSP total score was related to the participation communication score ( P < 0.0001), but not arousal or awareness subscale scores.…”
Section: Introductionmentioning
confidence: 97%
“…With the exception of amantadine, there is insufficient evidence to make any clear recommendations, and even in that case all that can be said is that it appears to be well tolerated, and may be beneficial. Considering that more rapid recovery from less responsive states improves readiness for rehabilitation and may improve outcomes [8], more study is clearly needed on this important topic.…”
Section: Discussionmentioning
confidence: 99%
“…About 15 % of children who experience a TBI will have moderate or severe injuries that include a period of decreased responsiveness [4]. Longer time to recovery from disorders of consciousness is predictive of worse prognosis after TBI [5, 6], and some reports suggest that shortening the period of disordered consciousness may improve outcomes, at least in part by increasing participation in rehabilitation treatment [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Although promoting arousal, or a state of wakefulness, may be an initial goal for children with disorders of consciousness, commonly the goal of intervention is to improve interaction with the environment, or responsiveness, in a child who is already aroused. The low levels of responsiveness in these patients threaten their ability to receive intensive rehabilitation interventions directed at optimizing their function, and limited access to rehabilitation services may in turn negatively affect the long‐term care and function of these children [5]. Opportunities for pharmaceutical intervention to improve responsiveness therefore are of great interest.…”
Section: Discussionmentioning
confidence: 99%